The effect of carbon tax on carbon emission abatement and GDP: a case study - Liu, X.; Leung, Yee-Hong; Xu, Y.; Yung, L. (Springer - Verlag, 2017)
© 2017, Springer-Verlag GmbH Germany. Carbon tax has been advocated as an effective economic instrument for the abatement of CO 2 emission by various countries, including China, the world’s biggest carbon emission country. However, carbon emission abatement cannot be done while ignoring the impact on economic growth. A delicate balance needs to be achieved between the two to find an appropriate pathway for sustainable development. This paper applies a multi-objective optimization approach to analyze the impact of levying carbon tax on the energy-intensive sectors of Guangdong province in China under the constraint of emission reduction target. This approach allows us to evaluate carbon emission minimization while maximizing GDP. For policy analysis, we construct five scenarios for evaluation and optimal choice. The results of the analysis show that a lower initial carbon tax rate is not necessarily better, and that a carbon tax is an effective means to reduce CO 2 emissions while maintaining a certain level of GDP growth.